Treatment of Carotid Artery Stenosis by Elective Stent Placement Instead of Carotid Endarterectomy in Patients with Severe Coronary Artery Disease - Michael Gross, C.; Krämer, Jochen; Uhlich, Frank; Tamaschke, Christian; Vogel, Peter; Friedrich, Ingrid; Dietz, Rainer; Waigand, Jürgen (Thrombosis and Haemostasis, 1999)
Patients with concomitant cardiac and cerebrovascular disease undergoing revascularization procedures are at high risk of both, cardiac and cerebrovascular complications. The purpose of our study was to evaluate the feasibility of prior elective carotid artery stenting as an alternative treatment procedure to carotid endarterectomy (CEA) in patients with concomitant coronary artery disease (CAD), who clearly needed coronary revascularization. We offered extracranial internal carotid stenting to 85 patients with 89 significant carotid stenoses. Out of these, 19 patients were symptomatic. The quantitative mean reduction in diameter was 77 ± 11%. Stent implantation was successful in 88 lesions. Two disabling major and 3 reversible minor strokes occurred periprocedurally. Three patients showed asymptomatic restenosis and stent deformation was detected in 2 patients. Based on this experience, carotid stenting in high risk patients with severe coronary artery disease is feasible and safe and might be indicated as an alternative procedure for combined surgery.
Keywords: Carotid stenosis; coronary artery disease; carotid endarterectomy; carotid stenting